Digital Democracy Transformation in Indonesia: Opportunities, Challenges, and Future Solutions - Wahidin, Darto; Utami, Ichwani Siti; Amalia, Aida Restu; Aqida, Alifia; Aidah, Salwa (Universitas of Muhammadiyah Makassar, 2025)
In the era of globalization, Indonesia's digital democracy faces significant challenges such as misinformation, privacy issues, and the digital divide, despite its high internet penetration. These certainly pose a major threat to the sustainability of digital democracy in Indonesia and the development of digital democracy in the future. Therefore, this study intends to analyze how Indonesia can effectively improve digital democracy while addressing these challenges. Using a systematic literature review method, this study examines literature published between 2019 and 2024, applying strict inclusion and exclusion criteria. Inclusion criteria include peer-reviewed articles and research reports directly related to democracy, public participation, and technology, published in Indonesian or English. Exclusion criteria eliminate irrelevant opinions, outdated publications before 2014, and studies with weak methodology. The study findings reveal that increasing digital literacy can significantly reduce political polarization caused by misinformation. In addition, this study emphasizes the need for collaboration between the government, society, and the private sector to promote inclusiveness, transparency, and accountability in the democratic process. In conclusion, this study recommends policies that prioritize digital literacy and technology development to create a sustainable digital democracy. The implementation of these policy recommendations can provide a framework for increasing public engagement and trust in democratic institutions, ultimately contributing to a more resilient and equitable digital democracy in Indonesia.